EFEKTIVITAS PENANGANAN TINDAK PIDANA PERIKANAN DI MALUKU UTARA - Muhammad Sofyan; Faisal Malik; Nam Rumkel (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
This paper aims to analyze the effectiveness of the application of Article 100 of Law Number 31 Year 2004 in handling fisheries crime in North Maluku. The type of research used is the research type Socio Legal Research. The data used is primary data which is data obtained directly from the object to be studied. Data is obtained through field research from the research locations mentioned above, namely in the form of interviews or statements from investigators of the Directorate General of Civil and Political Sciences, Public Prosecutors and District Court Judges, fisheries expert witnesses, and secondary data, namely data obtained from institutions or certain institutions. Data is obtained through report materials and other documents that have existed previously and have a close relationship with the issues discussed in this paper. The collected data were then analyzed qualitatively. The results of the study show that the application of Article 100 of Law Number 31 Year 2004 by law enforcement officials has not been effective, because investigators by the Police and prosecution by the Prosecutor consistently use these articles, but judges based on the trial decisions that occurred ignored the demands in article 100 by choosing the penalty is lighter because it only pays a fine in accordance with what happens in a fishery crime. Therefore, based on what happens repeatedly, it is imperative that in enforcing the fisheries criminal law in North Maluku, law enforcement officials, both the Police, the Attorney General as well as judges must be consistent in applying Article 100 since the process of investigation, prosecution and the decision to be decided.